2018
DOI: 10.2174/1389200219666180813144834
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation in Patients with Alzheimer’s Dementia - An Explorative Intervention Study

Abstract: Results show that the supplementation of Alzheimer's disease patients with a multispecies probiotic influences gut bacteria composition as well as tryptophan metabolism in serum. The correlation between Kyn/Trp and neopterin concentrations points to the activation of macrophages and/or dendritic cells. Further studies are warranted to dissect the potential consequences of Probiotic supplementation in the course of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 51 publications
(60 reference statements)
1
141
6
2
Order By: Relevance
“…[43] Another study in dementia showed a decrease in previously elevated zonulin levels after probiotic treatment as a possible hint towards an improvement. [37] Although we did not find any differences in stool zonulin and calprotectin levels, we found an increase in DAO levels which has been proven to be a valuable serum biomarker of gut barrier dysfunction. [44][45][46][47] Also, Ginko biloba, a commonly used phytotherapeutic drug in dementia, was able to reduce DAO levels in an animal model of alcoholic liver disease, indicating both the validity of DAO as a permeability biomarker and that gut permeability may be a modifiable and relevant therapeutic target.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…[43] Another study in dementia showed a decrease in previously elevated zonulin levels after probiotic treatment as a possible hint towards an improvement. [37] Although we did not find any differences in stool zonulin and calprotectin levels, we found an increase in DAO levels which has been proven to be a valuable serum biomarker of gut barrier dysfunction. [44][45][46][47] Also, Ginko biloba, a commonly used phytotherapeutic drug in dementia, was able to reduce DAO levels in an animal model of alcoholic liver disease, indicating both the validity of DAO as a permeability biomarker and that gut permeability may be a modifiable and relevant therapeutic target.…”
Section: Discussioncontrasting
confidence: 59%
“…[3] , [2] Recently an exploratory pilot study showed that probiotic modulation of the gut microbiome in dementia can lead to increased abundance of butyrate producing bacterial strains. [37] We also found that Clostridium clostridioforme and the genus Eisenbergiella increased with increasing cognitive impairment. Clostridium clostridioforme has mainly been described as a human pathogen [38] but has also been described to be associated with vegetarian diet.…”
Section: Discussionmentioning
confidence: 53%
“…Probiotic supplementation with Lactobacillus plantarum in combination with SSRI treatment improved cognitive performance and decreased Kyn concentrations in patients with major depression [compared to SSRI treatment alone, (266)]. Supplementation with a multispecies probiotic had a beneficial effect on Trp metabolism in trained athletes (267) and influenced Trp degradation and gut bacteria composition in patients with Alzheimer's disease (268). Additionally, highly adaptive lactobacilli where shown to produce the AhR ligand indole-3-aldehyde, which enabled IL-22 transcription for the fine tuning of host mucosal reactivity (269).…”
Section: Nutrition Microbiome and Physical Activity And Its Associamentioning
confidence: 99%
“…Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven. Additionally, the underlying mechanism has not been resolved.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Amentioning
confidence: 57%